L-Proline functionalized magnetic nanoparticles: A novel magnetically reusable nanocatalyst for one-pot synthesis of 2, 4, 6-triarylpyridines. Issue 1 (December 2018) - Maleki, Ali; Firouzi-Haji, Razieh
Abstract In this work, an efficient method for the immobilization ofL -proline on magnetic nanoparticles was offered and evaluated as a recoverable magnetic nanocatalyst for synthesis of 2, 4, 6-triarylpyridines through one-pot three-component reaction of acetophenone, aryl aldehydes and ammonium acetate. This article is the first report of the catalytic application ofL -proline functionalized magnetic nanoparticles in organic reactions as a magnetic nanocatalyst. This novel magnetic nanocatalyst proved to be effective and provided the products in high to excellent yield under solvent-free conditions. The structure of obtained nanoparticles was characterized by Fourier transform infrared spectrophotometry (FT-IR), field-emission scanning electron microscopy (FE-SEM), thermogravimetric analysis (TGA) and energy-dispersive X-ray spectroscopy (EDX). TGA result revealed that it is stable up to 200 °C for using as a catalyst in organic reactions. FE-SEM image of the synthesized nanocatalyst showed that it has nearly core-shell spherical shape and uniform size distribution with an average size about 80 nm. Moreover, the catalyst could be easily recovered by facile separation by magnetic forces and recycled for several times without significant loss of its catalytic activity. The benefits of this study are simplicity, nontoxicity, low cost, simple workup, and an environmentally benign nature.